A taxonomic revision of Gymnothorax undulatus (Anguilliformes: Muraenidae) in the Western Indian Ocean, with description of a new species - Sithole, Yonela; Smith, David G.; Mwale, Monica; Gouws, Gavin (Zootaxa, 2020)
The taxonomic status of the widely distributed Indo-Pacific undulated moray eel, Gymnothorax undulatus, is revised using morphological and genetics features. Ninety-seven specimens previously identified as G. undulatus were examined and their mitochondrial COI and 16S rRNA genes were analysed. The multivariate analysis of eight morphometric characters resulted in separation with little to no overlap among some geographic regions. These groupings explained more than 90% of the total variation, with 86.6% overall classification. Two color morphs were identified, and the South African population was described as new species, Gymnothorax elaineheemstrae n. sp., distinct from G. undulatus in having mottled and faintly reticulated color pattern, 134–136 total vertebrae and further confirmed by the genetic analysis of COI and 16S rRNA with > 0.1 genetic distance. The morphological and genetics results indicate that G. undulatus, previously treated as a single species, consists of more than one species.